2023
DOI: 10.1002/adma.202370043
|View full text |Cite
|
Sign up to set email alerts
|

Photolithography‐Based Microfabrication of Biodegradable Flexible and Stretchable Sensors (Adv. Mater. 6/2023)

Abstract: Microfabrication of Biodegradable Sensors In article number 2207081, Levent Beker and co‐workers report a photolithography‐based microfabrication process for bioresorbable devices. Consecutive application of sacrificial, adhesion and protection layers enable the use of delicate conductive and insulating bioresorbable materials through standard microfabrication processes. Using this approach, high‐density passive electric components and chemical sensors critical for transient electronics and implant application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…[11] Miniaturization, flexibility, and conformally adhering to human skin while maintaining their electrical features are significant factors that determine the functionality of flexible devices. [11,12] Realizing flexible electronic systems with these factors depends on the ability to perform scalable patterning of electronic materials on unusual substrates via various fabrication approaches, such as inkjet printing, [13] laser ablation, [14] and 3D printing. [15,16] The main limitation of these fabrication approaches is their lack of spatial resolution, making them incompatible with multiscale and massproduction device microfabrication.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…[11] Miniaturization, flexibility, and conformally adhering to human skin while maintaining their electrical features are significant factors that determine the functionality of flexible devices. [11,12] Realizing flexible electronic systems with these factors depends on the ability to perform scalable patterning of electronic materials on unusual substrates via various fabrication approaches, such as inkjet printing, [13] laser ablation, [14] and 3D printing. [15,16] The main limitation of these fabrication approaches is their lack of spatial resolution, making them incompatible with multiscale and massproduction device microfabrication.…”
Section: Introductionmentioning
confidence: 99%
“…[38,39] In addition, the capability of wafer-level and high-throughput fabrication makes photolithography economically practical, thereby enabling highly integrated circuit manufacturing. [12] Unfortunately, conventional photolithographic fabrication processes cannot accommodate the micro/nanofabrication of flexible devices because of the use of unusual substrate topologies and uneven surfaces, as well as damage to organic substrates by solvents and thermal loading, which affect device performance, including sensitivity, stability, and consistency. [12,24,39] For instance, photolithography requires a rigid substrate, such as silicon or glass, which limits the ability of the resulting devices to bend or stretch.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…8,9 Previous works have demonstrated that the design of micronano structures, 10,11 such as micropyramids 12,13 and micropillars, 14,15 are beneficial in achieving high sensitivity and a broad working range. 16,17 Traditional fabrication methods for these microsensing structures, such as nanomicro composite inks, optical lithography, 11,13,18 laser ablation, 19,20 vacuum disposition, 21 3D printing, 22,23 and other techniques, tend to be costly, complex, and time-consuming. 24−26 essential to develop an effective route to fabricate tactile sensors with a high performance.…”
Section: Introductionmentioning
confidence: 99%